Hygrothermal Effect on Composites Under In-Plane Fatigue at Stress Ratios of R = −1 and R = 0.1: An Analysis of Quasi-Isotropic Stitched Carbon Fibers - Shiino, Marcos Yutaka [UNESP]; de Siqueira, Guilherme Silva Moraes [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Montoro, Sérgio Roberto; Donadon, Maurício Vicente (Springer Nature, 2018)
The aeronautic structures normally operate under high levels of hygroscopic moisture from the surrounding environment at different temperature ranges while in service. Under such conditions, the behavior of laminate composite submitted to cyclic or static loadings can change drastically. In order to understand those effects in stitched fabrics, fatigue tests with open-hole specimens were carried out with a stress ratio of R = −1 and R = 0.1. The specimens were fatigue-tested as provided (environmental conditions) and after exposed to hygrothermal weathering conditions. Based on evidences from recent studies available in the open literature, e.g., effect of water diffusion on epoxy matrix, the overall results indicated a significant reduction in stiffness after the specimens are exposed to hygrothermal effects. The reduction in matrix stiffness, in this case, enhanced the fatigue strength in tension–tension load (R = 0.1) when compared to the specimens in normal conditions. The opposite occurs for the specimens loaded with stress ratio of R = −1, in which the delamination mechanisms changed during the loading reversion from tension to compression that promoted early delamination. Therefore, this process reduced the fatigue life of the specimens under hygrothermal condition. Then, by fractographic investigation, it was verified fracture patterns that regard to mode II damage in R = −1, in which mode II fracture toughness is known to decrease in the presence of water molecules.
Keywords: fatigue; hygrothermal; laminate; non-crimp fabric